Polyphenol profile by UHPLC-MS/MS, anti-glycation, antioxidant and cytotoxic activities of several samples of propolis from the northeastern semi-arid region of Brazil - Jadriane de Almeida Xavier; Iara Barros Valentim; Fabiana O. S. Camatari; Alberto M. M. de Almeida; Henrique Fonseca Goulart; Jamylle Nunes de Souza Ferro; Emiliano de Oliveira Barreto; Bruno Coelho Cavalcanti; Carla B. G. Bottoli; Marília Oliveira Fonseca Goulart (Taylor & Francis Group, 2017)
Context: Propolis has promising biological activities. Propolis samples from the Northeast of Bahia, Brazil - sample A from Ribeira do Pombal and B, from Tucano - were investigated, with new information regarding their biological activities. Objective: This paper describes the chemical profile, antioxidant, anti-glycation and cytotoxic activities of these propolis samples. Material and methods: Ethanol extracts of these propolis samples (EEP) and their fractions were analyzed to determine total phenolic content (TPC); antioxidant capacity through DPPH•, FRAP and lipid peroxidation; anti-glycation activity, by an in vitro glucose (10 mg/mL) bovine serum albumine (1 mg/mL) assay, during 7 d; cytotoxic activity on cancer (SF295, HCT-116, OVCAR-8, MDA-MB435, MX-1, MCF7, HL60, JURKAT, MOLT-4, K562, PC3, DU145) and normal cell lines (V79) at 0.04-25 μg/mL concentrations, for 72 h. The determination of primary phenols by ultra high-pressure liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS) and volatile organic compounds content by gas chromatography-mass spectrometry (GC-MS) were also performed. Results: The EEP polar fractions exhibited up to 90% protection against lipid peroxidation. The IC50 value for anti-glycation activity of EEP was between 16.5 and 19.2 μg/mL, close to aminoguanidine (IC50 = 7.7 μg/mL). The use of UHPLC-MS/MS and GC-MS allowed the identification of 12 bioactive phenols in the EEP and 24 volatile compounds, all already reported. Conclusions: The samples present good antioxidant/anti-glycation/cytotoxic activities and a plethora of biologically active compounds. These results suggest a potential role of propolis in targeting ageing and diseases associated with oxidative and carbonylic stress, aggregating value to them.